Pembelajaran Kewirausahaan Daring pada Masa Pandemi Covid-19 - Rani Novitasari; Indri Murniawaty; Siti Listyaningsih; Dwi Puji Astuti; Ahmad Sehabuddin (UM Purwokerto Press, 2021)
One solution to reduce unemployment is to create an entrepreneur in vocational school students through entrepreneurship learning. Efforts to prevent the spread of the Corona Virus in Indonesia have resulted in entrepreneurship learning being carried out online. The purpose of this study was to determine the implementation of online entrepreneurship learning, the obstacles faced when implementing online entrepreneurship learning and the strategies of the obstacles associated with learning entrepreneurship online at SMK YPPM, Boja District, Kendal Regency. The method used in this research is descriptive qualitative with data collection techniques, namely interviews, questionnaires with a Likert scale, and documentation. The results of this study are (1) Online entrepreneurship learning shows ineffective results. (2) The obstacles that arise during the implementation of online entrepreneurship learning for students are students who are not ready, unhappy, not interested in online entrepreneurship learning, lack of understanding of online learning media, inadequate internet networks, difficulty finding learning resources, unaccompanied, students cannot concentrate , students feel lazy, bored when learning entrepreneurship online and after learning entrepreneurship online students do not like reading books. Meanwhile, the obstacle for teachers is that it is difficult for teachers to find student grades because there are still many who do not collect assignments. (3) The strategy to reduce barriers is for the teacher to conduct a home visit. Shows very effective results and runs smoothly.